ANTIOXIDANT ACTIVITY TEST of SIJUKKOT (Lactuca indica L.) LEAVES EXTRACT LEAF - Sumiati Nainggolan; Ida Duma Riris (Indonesian Journal of Chemical Science and Technology (IJCST), 2020)
Has been investigated the antioxidant activity of  sijukkot ( Lactuca indica L.) The antioxidant activity was tested by capturing 2,2’-diphenyl-picrylhydrazyl (DPPH) free radical method and Vitamin C as a standard of comparison, to absorption using UV-Vis  spectrophotometry at a wavelength of 517nm. The data obtained were analyzed using the SPSS for windows, resulting in a value of y = 0.2036x + 30.35 for sijukkot extract and y = 29.625x - 73.664 for vitamin C. It was found the leaves have an antioxidant site with 96,51 ppm through IC50 test 4,17 ppm which used Vitamin C as a control.